Effects of reaction time and hydrochloric acid concentration on acid hydrolysis of rice husk by reflux method - Kanatip Kumproa (2018)
Thailand has a large amount of lands for the rice cultivation which ranked as the fifth of the world and stays on its position as the world's largest rice exporter. A huge number of biomass wastes from the rice mill process, rice husk, lead to the environmental problems in Thailand. However, there is an alternative way to turn this waste into an advantage. Rice husk is full of lignocellulose and SiO2; therefore, it becomes a great and resource of the biomass material for the chemical and biological production. Lignin and hemicellulose from rice husk could be extracted and hydrolysed by base and acid solution, respectively. The aims of this work were to extract lignin and to hydrolyse hemicellulose from rice husk; furthermore, this work was to determine the optimum concentration of acid solution and reaction time for hemicellulose extraction. Rice husk was dried and then milled to obtain the average particle diameter of 355 μm. The lignin extraction was performed in term of NH4OH solution (10% v/v) at 25oC for 24 h with dual-action shakers. Then, the hemicellulose was hydrolyzed by HCl solution (2, 4, 6 and 8% v/v) using a solid/liquid ratio of 1g dry weight/20 ml of HCl solution and heated at 100oC for 3 and 5 h with reflux method. The samples were characterized by UV spectrophotometer and scanning electron microscope (SEM-EDS). The results indicated that the lignin content was 12.3% w/w when applying of 10% v/v of NH4OH. Moreover, the highest hemicellulose content (35.5 %w/w) was obtained by 6% v/v of HCl at 100oC for 5 h. Scanning electron micrograph showed that the rice husk composed of cell wall and cellulose fibers. These cellulose fibers were separated by removing lignin and hemicellulose. According to, the EDS analysis showed that the only rice husk cell wall consists of SiO2. © (2012) Trans Tech Publications, Switzerland.